PENGELOLAAN OBJEK WISATA ISTANO BASA PAGARUYUNG DI KABUPATEN TANAH DATAR - Rinche Rinaldi; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Tourism is something done by someone or more with the aim among others to get kenikamatan and meet the desire to know something. Based on field observation there are some problems concerning the management of Istano Basa Pagaruyung tourist object in Tanah Datar regency which is management of Istano Basa Pagaruyung tourism object is not good, human resources are still minimal, and lack of promotion of tourism object. It deserves the attention of the government to be more active in the management of Istano Basa Pagaruyung tourist attraction in Tanah Datar regency. The purpose of this research is to know the management of Istano Basa Pagaruyung tourism object in Tanah Datar regency and factors influencing the management of Istano Basa Pagaruyung tourism object in Tanah Datar regency.The concept of theory used is the management theory by George R. Terry which starts fromplanning, organizing, moving, and supervision. This research uses qualitative descriptive research method. The type of data used is primary data and secondary data. In the data collecting researchers using observation techniques, interviews, and literature study. Interviews were conducted with informants namely Head of Tourism, Head of UPT, and cashier of tourism promotion.The results of this study resulted in the conclusion that the management of Istano Basa Pagaruyung tourist attraction in Tanah Datar Regency has not been maximized. Then there are still lack of factors that influence in the management of Istano Basa Pagaruyung tourist attraction in Tanah Datar regency that is budget, human resources, facilities and infrastructure.Keywords: Management, Tourist Attraction